Do eating behaviors in the general population account for country variance in glycemic control among adolescents with diabetes: the Hvidoere Study Group and the Health Behaviour in School‐Aged Children study. Issue 8 (17th June 2013) - Due, Pernille; de Beaufort, Carine; Damsgaard, Mogens Trab; Mortensen, Henrik Bindesbøl; Rasmussen, Mette; Ahluwalia, Naman; Skinner, Timothy; Swift, Peter; ,
<x xml:space="preserve">Abstract</x> Background The Hvidoere Study Group (HSG) has demonstrated major differences in glycemic control between pediatric diabetes centers which remain largely unexplained. This study investigates whether these differences are partly attributable to healthy eating norms in the background population. Methods The study involved adolescents from 18 countries from (i) the Health Behaviour in School‐Aged Children study (HBSC) and (ii) the HSG. There were 94 387 participants from representative HBSC samples of 11‐, 13‐ and 15‐yr‐olds and 1483 11‐ to 15‐yr‐old adolescents with diabetes from the HSG. The frequency of intake of fruit, vegetables, sweets, sugary soft drinks, and daily breakfast was compared between the two groups. The glycemic control of the adolescents in the HSG cohort was determined by measuring glycated hemoglobin (HbA1c). Results Across countries in the HSBC survey, there was substantial variation in prevalence of healthy eating behavior and even greater variation between adolescents from the HSG centers. In all countries more adolescents with diabetes reported healthy eating behavior compared to national norms. In individuals healthy eating behavior had a significant effect on the individual level HbA1c. There was no significant correlation between the frequencies of these healthy eating behaviors at (i) the national level and (ii) diabetes center level and the center mean HbA1c. Conclusions Although individual healthy eating behavior is associated with better glycemic control at the individual level, such eating behavior does not explain the center differences in HbA1c. Similarly, the reported healthy eating norm of the background populations does not explain the variation in glycemic control among centers.